Porous composite gel electrolyte and preparation method thereof and semi-solid lithium ion battery
By using porous composite gel electrolytes in lithium-ion batteries, using the composite of poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate) and the introduction of basalt fibers, the problem of insufficient mechanical strength and thermal stability of gel electrolytes in lithium-ion batteries is solved, and higher electrochemical performance and electrode interface stability are achieved.
Patent Information
- Application Number
- CN202310450134.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-04-24
AI Technical Summary
The polymer gel electrolytes of existing lithium-ion batteries have shortcomings in terms of mechanical strength and thermal stability, and have poor interfacial contact with the electrodes, which affects the safety and performance of the battery.
Using porous composite gel electrolyte, poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate) are combined and basalt fibers are introduced to improve the mechanical strength and thermal stability of the gel electrolyte and improve the interfacial contact with the electrode.
It significantly improves the mechanical strength and thermal stability of the gel electrolyte, enhances the electrochemical performance and the interface stability of the electrode, and improves the ionic conductivity of the electrolyte.
Smart Images

Figure CN116247292B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a porous composite gel electrolyte and a preparation method thereof, and a semi-solid lithium ion battery. Background Art
[0002] With the vigorous development of the energy storage industry in recent years, the requirements for the safety of lithium-ion batteries have also been increasing. Polymer gel electrolytes have a high ionic conductivity close to that of liquid electrolytes and effectively reduce electrolyte leakage, which greatly ensures the safety of lithium-ion batteries and shows excellent application prospects.
[0003] In the selection of polymer matrix materials, poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) and poly(methyl methacrylate) (PMMA) have attracted much attention due to their good performance. As an excellent material, PVDF-HFP has the advantages of corrosion resistance, temperature resistance, easy film preparation, high dielectric constant, etc. Its crystallinity is also much lower than that of similar PVDF. The gel polymer electrolyte prepared with PVDF-HFP can show higher room temperature conductivity. The carbonyl group of PMMA makes it more compatible with the electrolyte, which can improve the wettability of the blended diaphragm to the electrolyte. In addition, PMMA has good interface stability to the lithium electrode, but its mechanical strength after gel activation is poor and its thermal stability is not good.
[0004] Therefore, it is necessary to study new polymer gel electrolytes to meet the needs of the development of the energy storage industry. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems:
[0006] CN110943258A provides a PVDF-HFP composite lignocellulose gel polymer electrolyte membrane, which combines the excellent electrochemical properties of lignocellulose and PVDF-HFP, while improving the mechanical strength of the composite membrane; however, PVDF-HFP has poor contact with electrode materials and has interface problems.
[0007] CN110010829B provides a PVDF-HFP / PMMA / CMC composite membrane, which includes a stacked PVDF-HFP / PMMA film and a CMC film, and is prepared by a direct coating and drying method, and the ion conductivity can reach 4.388mS / cm. However, the membrane lacks the introduction of high-strength inorganic fillers, so that its mechanical properties are slightly insufficient, and the preparation by the direct coating and drying method is not conducive to forming a porous structure.
[0008] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention proposes a porous composite gel electrolyte, which uses poly (vinylidene fluoride-hexafluoropropylene) and poly (methyl methacrylate) in combination to reduce the crystallinity of the polymer matrix, while improving the interface problem between poly (vinylidene fluoride-hexafluoropropylene) and the electrode, and further introduces basalt fiber, which effectively improves the mechanical strength and thermal stability of the gel electrolyte, reduces the crystallinity of the polymer matrix, and improves the conductivity of the electrolyte.
[0009] The porous composite gel electrolyte of the embodiment of the present invention includes: poly(vinylidene fluoride-hexafluoropropylene), poly(methyl methacrylate) and basalt fiber.
[0010] The advantages and technical effects brought by the porous composite gel electrolyte of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate) are introduced at the same time. The composite use of the two can improve the poor interface contact between poly(vinylidene fluoride-hexafluoropropylene) and the electrode, the poor mechanical strength of poly(methyl methacrylate) gel after activation, and the poor thermal stability, effectively improving the crystallinity of the polymer film, enhancing the electrochemical properties of the gel electrolyte and the interface stability of the electrode; 2. In the embodiment of the present invention, the mechanical strength of the gel electrolyte is further enhanced by introducing basalt fiber, and the crystallinity of the polymer matrix is reduced, the conductivity of the gel electrolyte is improved, and the thermal stability of the gel electrolyte is improved; 3. In the embodiment of the present invention, the gel electrolyte with a porous structure can absorb more electrolyte, and correspondingly has more free Li + quantity, so that the composite gel electrolyte has greater ionic conductivity.
[0011] In some embodiments, the mass ratio of the poly(vinylidene fluoride-hexafluoropropylene) to poly(methyl methacrylate) is 20:1 to 1:20.
[0012] In some embodiments, the mass of the basalt fiber is 10-100% of the sum of the mass of the poly(vinylidene fluoride-hexafluoropropylene) and the poly(methyl methacrylate).
[0013] In some embodiments, the basalt fiber includes at least one of basalt fiber chopped strands, basalt fiber coarse ground powder and basalt fiber fine powder; preferably, the length of the basalt fiber chopped strands is >1 mm, the particle size of the basalt fiber coarse ground powder is 100 μm to 1 mm, and the particle size of the basalt fiber fine powder is 20 μm to 100 μm.
[0014] In some embodiments, the porous composite gel electrolyte also includes a lithium-ion battery electrolyte.
[0015] The present invention also provides a method for preparing the porous composite gel electrolyte, comprising the following steps:
[0016] (1) dissolving poly(vinylidene fluoride-hexafluoropropylene), poly(methyl methacrylate), basalt fiber and a pore-forming agent in a solvent to obtain a coating solution;
[0017] (2) coating the coating liquid obtained in step (1) on a substrate, and then immersing the substrate coated with the coating liquid in deionized water for phase separation and film formation to obtain a polymer film;
[0018] (3) Drying the polymer film obtained in step (2) and immersing it in an electrolyte to obtain a porous composite gel electrolyte.
[0019] The advantages and technical effects brought by the preparation method of the porous gel electrolyte of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention dissolves basalt fiber, poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate) in a solvent, so that the basalt fiber is evenly dispersed in the polymer matrix, which effectively improves the interface problem; 2. The method of the embodiment of the present invention adds a pore-forming agent during the preparation process, which can increase the porosity of the polymer film and thereby improve the liquid absorption rate of the gel electrolyte and enhance its ionic conductivity; 3. The method of the embodiment of the present invention has a simple preparation process and is easy to operate, which is convenient for promotion and application in industrial production.
[0020] In some embodiments, in step (1), the solvent includes at least one of DMF, NMP, and DMSO, and the mass of the solvent is 2 to 10 times the sum of the masses of poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate); and / or the pore-forming agent is polyethylene oxide, and the mass of the pore-forming agent is 2 to 10% of the sum of the masses of poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate).
[0021] In some embodiments, in step (2), the soaking time in the deionized water is 2 to 12 hours.
[0022] In some embodiments, in step (3), the immersion time in the electrolyte is 0.1 to 10 hours.
[0023] An embodiment of the present invention further provides a semi-solid lithium ion battery, comprising the porous composite gel electrolyte or the porous composite gel electrolyte prepared by the method.
[0024] The advantages and technical effects brought by the semi-solid lithium ion battery in the embodiment of the present invention, the semi-solid lithium ion battery in the embodiment of the present invention has all the technical features of the porous composite gel electrolyte in the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the porous composite gel electrolyte in the embodiment of the present invention, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 is a cycle performance diagram of a lithium-ion battery assembled with the electrolyte prepared in Example 1, a graphite negative electrode, and a lithium iron phosphate positive electrode;
[0026] Figure 2 This is a cycle performance diagram of a lithium-ion battery assembled with the electrolyte prepared in Example 1, a graphite negative electrode, and a lithium iron phosphate positive electrode. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0028] The porous composite gel electrolyte of the embodiment of the present invention includes: poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), poly(methyl methacrylate) (PMMA) and basalt fiber.
[0029] The porous composite gel electrolyte of the embodiment of the present invention introduces PVDF-HFP and PMMA at the same time. The composite use of the two can improve the poor interface contact between PVDF-HFP and the electrode, the poor mechanical strength of PMMA gel after activation, and the poor thermal stability, effectively improve the crystallinity of the polymer film, enhance the electrochemical properties of the gel electrolyte and the interface stability of the electrode; the mechanical strength of the gel electrolyte is further enhanced by introducing basalt fiber, and the crystallinity of the polymer matrix is reduced, the conductivity of the gel electrolyte is improved, and the thermal stability of the gel electrolyte is improved; the gel electrolyte with a porous structure can absorb more electrolyte, and correspondingly has more free Li + quantity, so that the composite gel electrolyte has greater ionic conductivity.
[0030] In some embodiments, preferably, the mass ratio of the PVDF-HFP to PMMA is 20:1 to 1:20. Further preferably, the mass ratio of the poly-PVDF-HFP to PMMA is 12:1 to 4:1.
[0031] In the implementation of the present invention, the dosage ratio of PVDF-HFP and PMMA is optimized, which can further enable the porous structure formed by PVDF-HFP and the excellent electrolyte wettability of PMMA to have a good synergistic effect, which is beneficial to improving the comprehensive performance of the gel electrolyte; if the dosage of PVDF-HFP is too much, it is not conducive to improving the interface contact performance between the electrolyte and the electrode; if the dosage of PMMA is too much, it is not conducive to improving the mechanical strength of the electrolyte.
[0032] In some embodiments, preferably, the mass of the basalt fiber is 10-100% of the sum of the mass of the PVDF-HFP and PMMA. Further preferably, the mass of the basalt fiber is 30-50% of the sum of the mass of the PVDF-HFP and PMMA.
[0033] In the embodiment of the present invention, the amount of basalt fiber is optimized, which can effectively improve the mechanical properties and thermal stability of the gel electrolyte; if the amount of basalt fiber is too little, the improvement of the mechanical properties and thermal stability of the gel electrolyte is limited; if the amount of basalt fiber is too much, agglomeration will occur in the polymer matrix, which is not conducive to the improvement of the mechanical properties.
[0034] In some embodiments, preferably, the basalt fiber comprises at least one of basalt fiber chopped strands, basalt fiber coarse ground powder and basalt fiber fine powder; preferably, the length of the basalt fiber chopped strands is greater than 1 mm, the particle size of the basalt fiber coarse ground powder is 100 μm to 1 mm, and the particle size of the basalt fiber fine powder is 20 μm to 100 μm. Further preferably, the basalt fiber is basalt fiber coarse ground powder.
[0035] In some embodiments, preferably, the porous composite gel electrolyte also includes a lithium-ion battery electrolyte.
[0036] The present invention also provides a method for preparing the porous composite gel electrolyte, comprising the following steps:
[0037] (1) dissolving PVDF-HFP, PMMA, basalt fiber and pore-forming agent in a solvent to obtain a coating solution;
[0038] (2) coating the coating liquid obtained in step (1) on a substrate, and then immersing the substrate coated with the coating liquid in deionized water for phase separation and film formation to obtain a polymer film;
[0039] (3) Drying the polymer film obtained in step (2) and immersing it in an electrolyte to obtain a porous composite gel electrolyte.
[0040] The method for preparing the porous gel electrolyte of the embodiment of the present invention dissolves basalt fiber, PVDF-HFP and PMMA in a solvent, so that the basalt fiber is evenly dispersed in the polymer matrix, which effectively improves the interface problem; adding a pore-forming agent during the preparation process can increase the porosity of the polymer film and thus improve the liquid absorption rate of the gel electrolyte and improve its ionic conductivity; the preparation process is simple and easy to operate, which is convenient for promotion and application in industrial production.
[0041] In some embodiments, preferably, in step (1), the solvent includes at least one of DMF, NMP, and DMSO, and the mass of the solvent is 2 to 10 times the sum of the masses of PVDF-HFP and PMMA; and / or, the pore-forming agent is polyethylene oxide (PEO), and the mass of the pore-forming agent is 2 to 10% of the sum of the masses of PVDF-HFP and PMMA.
[0042] In the embodiment of the present invention, the amount of solvent is preferably selected to promote the dissolution of PVDF-HFP, PMMA and basalt fiber to form a uniform solution; PEO is preferably used as a pore-forming agent. PEO as a pore-forming agent is different from other liquid pore-forming agents such as n-butanol. It dissolves relatively slowly during the phase separation and film formation process when immersed in deionized water, which will make the formed pore structure more uniform, and there will be no problem of through-holes or pore structure collapse caused by rapid dissolution of a large amount of pore-forming agents; the amount of PEO is further optimized, which helps to form a porous electrolyte, thereby improving the liquid absorption rate of the polymer membrane and improving the ionic conductivity of the gel electrolyte.
[0043] In some embodiments, preferably, the step (1) further comprises stirring to obtain the coating solution, and ultrasonically vibrating or vacuum-assisted removal of bubbles from the coating solution. Further preferably, the stirring time is 1 to 10 hours. More preferably, the stirring time is 4 to 6 hours.
[0044] In the embodiment of the present invention, the stirring process can form a uniform coating solution, and the degassing process can reduce the bubble content in the polymer film, reduce defects, and further ensure the quality of the prepared gel electrolyte.
[0045] In some embodiments, preferably, in step (2), the soaking time in the deionized water is 2 to 12 hours. Further preferably, the soaking time in the deionized water is 5 to 8 hours.
[0046] In the embodiment of the present invention, soaking in deionized water helps to separate the polymer film from the glass plate. The soaking time in deionized water is preferably selected to ensure that the organic solvent and the PEO pore former are completely dissolved, thereby reducing the impurity content in the gel electrolyte.
[0047] In some embodiments, preferably, in step (3), the drying process comprises wiping off the moisture on the surface of the polymer film and then placing the film in an oven at 40 to 60° C. for drying for 2 to 24 hours. More preferably, the drying time is 10 to 24 hours.
[0048] In some embodiments, preferably, in step (3), the immersion time in the electrolyte is 0.1 to 10 hours. Further preferably, the immersion time in the electrolyte is 0.5 to 2 hours.
[0049] An embodiment of the present invention further provides a semi-solid lithium-ion battery, comprising the porous composite gel electrolyte or the porous composite gel electrolyte prepared by the method.
[0050] The semi-solid lithium-ion battery of the embodiment of the present invention has all the technical features of the porous composite gel electrolyte of the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the porous composite gel electrolyte of the embodiment of the present invention, which will not be repeated here.
[0051] In some embodiments, preferably, the semi-solid lithium-ion battery further comprises a positive electrode and a negative electrode. Further preferably, the positive electrode comprises at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide; and the negative electrode comprises at least one of graphite, biomass carbon, silicon-carbon composite material, and metallic lithium.
[0052] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0053] Example 1
[0054] (1) PVDF-HFP and PMMA were dissolved in DMF solvent at a mass ratio of 9:1, where the mass of DMF solvent was 5 times the total mass of PVDF-HFP and PMMA; 40% basalt fiber powder (based on the total mass of PVDF-HFP and PMMA) was added; and then 5% PEO was added as a pore-forming agent (based on the total mass of PVDF-HFP and PMMA);
[0055] (2) stirring the mixed solution obtained in step (1) for 5 h;
[0056] (3) then performing ultrasonic oscillation to remove bubbles and obtain a coating solution;
[0057] (4) applying the coating liquid obtained in step (3) evenly and evenly on a glass plate; immersing the glass plate with the coating liquid on its surface horizontally and uniformly in deionized water for phase separation and film formation, and immersing the glass plate so that the organic solvent and the PEO pore-forming agent are completely dissolved, the immersion time is 6 hours;
[0058] (5) Take out the polymer film from the deionized water, gently wipe off the surface moisture, and put it into a 50°C oven for drying to completely remove moisture. The drying time is 12 h;
[0059] (6) Soak the polymer film obtained in step (5) in the electrolyte for 1 hour to allow it to fully absorb the electrolyte to form a gel, and the soaking time is 1 hour. Finally, a PVDF-HFP / PMMA / basalt fiber porous composite gel electrolyte is obtained.
[0060] Embodiments 2 to 6
[0061] The preparation methods of Examples 2 to 6 are the same as that of Example 1, except that the ratio of PVDF-HFP to PMMA in step (1) is adjusted to 18:1, 12:1, 6:1, 4:1, and 1:1, respectively.
[0062] Embodiments 7 to 10
[0063] The preparation methods of Examples 7 to 10 are the same as those of Example 1, except that the amount of basalt fiber added in step (1) is adjusted to 10%, 30%, 50%, and 100%, respectively.
[0064] Examples 11 to 13
[0065] The preparation methods of Examples 11 to 13 are the same as those of Example 1, except that the amount of PEO added in step (1) is adjusted to 1%, 2%, and 10%, respectively.
[0066] Embodiments 14 to 17
[0067] The preparation methods of Examples 14 to 17 are the same as those of Example 1, except that the soaking time in deionized water after phase separation and membrane formation in step (4) is adjusted to 1 h, 5 h, 8 h, and 15 h, respectively.
[0068] Embodiments 18 to 20
[0069] The preparation methods of Examples 18 to 20 are the same as those of Example 1, except that the drying time of the polymer film in step (5) is adjusted to 10 h, 24 h, and 30 h, respectively.
[0070] Examples 21 to 24
[0071] The preparation methods of Examples 21 to 24 are the same as those of Example 1, except that the immersion time of the polymer film in the electrolyte in step (5) is adjusted to 0.1 h, 0.5 h, 2 h, and 10 h, respectively.
[0072] Comparative Example 1
[0073] The preparation method of this comparative example is the same as that of Example 1, except that the amount of PEO added in step (1) is adjusted to 20%.
[0074] Comparative Example 2
[0075] The preparation method of this comparative example is the same as that of Example 1, except that the basalt fiber in step (1) is replaced by nano-silicon dioxide.
[0076] Comparative Example 3
[0077] The preparation method of this comparative example is the same as that of Example 1, except that the PEO pore-forming agent in step (1) is replaced by n-butanol.
[0078] The electrolyte prepared in Example 1 and Comparative Example 1 was assembled into a lithium-ion battery with an ink negative electrode and a lithium iron phosphate positive electrode, and its cycle performance was tested under the following test conditions: a cyclic charge and discharge test was performed at a current rate of 0.5C; the test results are shown in FIG. Figure 1 and Figure 2 shown.
[0079] The properties of the gel electrolytes prepared in Examples 1 to 24 and Comparative Examples 1 to 3 were tested, wherein the mechanical properties were tested under the following conditions: room temperature tensile test; the test results are shown in the following table:
[0080] Table 1 Effects of different ratios of PVDF-HFP:PMMA on the performance of gel electrolyte
[0081]
[0082] According to Examples 1 to 6, it can be seen that as the ratio of PMMA to PVDF-HFP increases, the liquid absorption rate of the gel electrolyte increases first and then decreases, and the ionic conductivity changes in the same manner as the liquid absorption rate. This is the result of the synergistic effect of the porous structure formed by PVDF-HFP and the excellent electrolyte wettability of PMMA. In addition, if the PMMA content is too high, the tensile strain of the gel electrolyte will be reduced, that is, the toughness will be lost to a certain extent.
[0083] Table 2 Effect of different basalt fiber contents on gel electrolyte performance
[0084]
[0085] According to the data in the above table, it can be seen that with the increase of basalt fiber content, the liquid absorption rate of gel electrolyte gradually decreases. This is because basalt fiber blocks part of the pore structure. The change law of ionic conductivity is basically consistent with the change of liquid absorption rate. The reason why the ionic conductivity of Example 9 is relatively higher than that of Example 8 is that the addition of basalt fiber can reduce the crystallinity of the polymer to a certain extent and improve the ionic conductivity. Under the condition of similar liquid absorption rate, the effect of this reduction in crystallinity on ionic conductivity begins to manifest. In addition, if the content of basalt fiber is too low, the mechanical strength of the gel electrolyte will be limited; if the content of basalt fiber is too high, the toughness of the gel electrolyte will be lost to a certain extent.
[0086] Table 3 Effect of different PEO pore-forming agent contents on gel electrolyte performance
[0087]
[0088] According to the data in Table 3, it can be seen that too little pore-forming agent will result in a lower porosity of the prepared gel electrolyte, thereby reducing the ionic conductivity; with the increase of the PEO pore-forming agent content, the prepared gel electrolyte has an increased porosity, which increases the liquid absorption rate and ionic conductivity; however, when the amount of PEO pore-forming agent is too much, the excessive pore structure of the gel electrolyte will reduce the mechanical properties of the gel electrolyte.
[0089] Table 4 Effect of different phase separation immersion time on the performance of gel electrolyte
[0090]
[0091]
[0092] According to the data in Table 4, it can be seen that if the phase separation immersion time is too short, the solvent and PEO pore former are not completely dissolved, and the undissolved PEO will fill in the pores, reducing the liquid absorption rate to a certain extent. However, the residual solvent and pore former will also reduce the crystallinity of the gel electrolyte to a certain extent. Therefore, the ionic conductivity of Example 14 is slightly higher than the ionic conductivity of the gel electrolyte at a similar liquid absorption rate. If the phase separation immersion time is too long, it will not have a significant effect on the performance of the gel electrolyte, because the solvent and PEO pore former have been completely dissolved.
[0093] Table 5 Effect of different drying time on the performance of gel electrolyte
[0094]
[0095] According to the data in Table 5, it can be seen that if the drying time is too long, the water has been completely removed. Although it will not have a significant impact on the performance of the gel electrolyte, it will reduce production efficiency and increase the time cost of industrial production.
[0096] Table 6 Effect of different electrolyte immersion time on gel electrolyte performance
[0097]
[0098]
[0099] According to the data in Table 6, it can be seen that a short immersion time in the electrolyte reduces the liquid absorption rate of the gel electrolyte, thereby reducing the ionic conductivity; too long immersion time in the electrolyte does not have a significant effect on the performance of the gel electrolyte. The reason is that the electrolyte has been completely infiltrated. Prolonging the time does not increase the liquid absorption rate, but it will reduce production efficiency and increase the time cost of industrial production.
[0100] Table 7
[0101]
[0102] According to the data in Table 7, in Comparative Example 2, the basalt fiber is replaced with a smaller nano-silicon dioxide material. Since the nano-silicon dioxide material is easy to agglomerate, the mechanical strength is not as good as the gel electrolyte with basalt fiber added, and its smaller size will fill the pore structure, resulting in a decrease in liquid absorption, thereby reducing the ionic conductivity. In Comparative Example 3, after the pore former is changed from PEO to liquid n-butanol, the dissolution rate of n-butanol is accelerated during the phase separation process, which makes the pore structure uniform, and it is easy to collapse and shrink some pores, thereby reducing the liquid absorption rate and mechanical strength of the electrolyte membrane.
[0103] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0104] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a porous composite gel electrolyte, characterized in that: The following steps are involved: (1) dissolving poly(vinylidene fluoride-hexafluoropropylene), poly(methyl methacrylate), basalt fiber and a pore-forming agent in a solvent to obtain a coating solution; (2) coating the coating liquid obtained in step (1) on a substrate, and then immersing the substrate coated with the coating liquid in deionized water for phase separation and film formation to obtain a polymer film; (3) drying the polymer film obtained in step (2) and immersing it in an electrolyte to obtain a porous composite gel electrolyte; The prepared porous composite gel electrolyte includes: poly(vinylidene fluoride-hexafluoropropylene), poly(methyl methacrylate) and basalt fiber; The mass of the basalt fiber is 30-50% of the sum of the mass of the poly(vinylidene fluoride-hexafluoropropylene) and the poly(methyl methacrylate); The pore-forming agent is polyethylene oxide, and the mass of the pore-forming agent is 2-5% of the sum of the mass of poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate).
2. The method for preparing the porous composite gel electrolyte according to claim 1, characterized in that: The mass ratio of the poly(vinylidene fluoride-hexafluoropropylene) to the poly(methyl methacrylate) is 20:1 to 1:
20.
3. The method for preparing the porous composite gel electrolyte according to claim 1, characterized in that: The basalt fiber includes at least one of chopped basalt fiber, coarsely ground basalt fiber powder and fine basalt fiber powder.
4. The method for preparing the porous composite gel electrolyte according to claim 3, characterized in that: The length of the chopped basalt fiber strands is greater than 1 mm, the particle size of the coarsely ground basalt fiber powder is between 100 μm and 1 mm, and the particle size of the fine basalt fiber powder is between 20 μm and 100 μm.
5. The method for preparing the porous composite gel electrolyte according to claim 1, characterized in that: In the step (1), the solvent comprises at least one of DMF, NMP and DMSO, and the mass of the solvent is 2 to 10 times the sum of the masses of poly(vinylidene fluoride-hexafluoropropylene) and poly(methyl methacrylate).
6. The method for preparing the porous composite gel electrolyte according to claim 1, characterized in that: In the step (2), the soaking time in the deionized water is 2 to 12 hours.
7. The method for preparing the porous composite gel electrolyte according to claim 1, characterized in that: In the step (3), the immersion time in the electrolyte is 0.1 to 10 hours.
8. A semi-solid lithium-ion battery, characterized in that: A porous composite gel electrolyte prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
PVDF-HFP / PMMA / CMC composite membrane, its preparation method and application
CN110010829B
PVDF-HFP composite lignocellulose gel polymer electrolyte membrane and preparation method thereof
CN110943258A
Polymer membrane, preparation method thereof, electrolyte possessing polymer membrane and cell
CN104177738A
Hierarchical porous structure gel polymer electrolyte membrane and preparation method thereof
CN105186033A
Organogel polymer electrolytic solution, preparation method, application, sodium-based dual-ion battery and preparation method thereof
CN109638344A